Commissioning and exploitation of the  Tomo experimental station: case studies - Filosa, Raffaele; Cipparrone, Gabriella; Formoso, Vincenzo (Università della Calabria, 2021)
At the University of Calabria, the MATERIA project for the creation of a research infrastructure on advanced materials and technologies is being implemented. The MATERIA scientific centre will have a multidisciplinary nature and will be available not only to all University researchers but will also offer advanced services to the entire national and international scientific community. The core of the MATERIA project is STAR (Southern european Thomson source for Applied Research), an advanced Thomson source of monochromatic tunable, ps-long, polarized X-ray beams, ranging from 20 to 140 keV. The X-rays will be devoted to experiments of matter science, cultural heritage, advanced radiological imaging with micro-tomography capabilities. Thomson Back-Scattering (TBS) X-Ray sources, nowadays, are attracting strong attention, mainly by a strong flexibility, compactness and less expensive, respect to the synchrotron sources. (Bacci et al. 2014). The TBS is the electromagnetic process in which each electron absorbs one (linear Thomson scattering) or more (nonlinear Thomson scattering) photons from a laser pulse, emitting one photon. (Curatolo et al. 2017). If the electrons are ultrarelativistic the frequency of the scattered radiation is upshifted and it is emitted forward with respect to the particles motion, with a small aperture cone, proportional to the inverse of the Lorentz relativistic factor. A TBS source driven by high quality electron beams can works in different operating modes, e.g.: the high-fluxmoderate- monochromaticity mode, suitable for medical imaging when high-flux sources are needed; the moderate-flux- monochromatic mode, suitable to improve the detection/dose performance; short-and monochromatic mode, useful for pump-and-probe experiments; further the coherence properties of the radiation have been well investigated by phase contrast imaging and diffraction enhanced imaging. The STAR source is based on: One S-band RF Gun at 100 Hz that will produce electron bunches boosted up to 60 MeV by a 3m long S-band TW cavity. A dogleg convey the beam on a parallel line, so to shield the X-ray line from the background radiation due to Linac dark current. The peculiarity of the machine is the ability to produce high quality electron beams, with low emittance and high stability, allowing to reach spot sizes around 15-20 microns, with a pointing jitter of the order of a few microns. The collision laser will be based on a Yb:Yag 100 Hz high quality laser system, synchronized to an external photo-cathode laser and to the RF system to better than 1 ps time jitter. As a first application of the STAR source it was decided to build an experimental station (beamline) dedicated to X-ray microtomography. X-ray microtomography is a kind of computed axial tomography (commonly abbreviated as CT), characterized by a high spatial resolution. It is a non-destructive 3-dimensional imaging technique used to investigate the internal microstructure of small samples (whose size is of a few centimeters), for which no particular sample preparation is required. The outcome of an X-ray microtomography investigation is a set of bidimensional grayscale scans of the sample, which are elaborated by Computed tomographic reconstruction algorithms in order to produce a highly resolved 3-D reconstruction of the sample, having a typical resolution of the order of a micron or even smaller, depending on the sample size. The quality of the final images relies on the different X-ray absorption properties of the materials that constitute the sample. In particular, the grayscale of the outcome image, and so its contrast level, is correlated to the density, composition and thickness of the sample materials, and it is due to the detection of amplitude variations of the transmitted X-rays. X-ray microtomography is used in materials studies, in particular for composites, for which it is very important to obtain morphological and densitometric information by using a noninvasive and a non-destructive investigation technique. The work presented in this thesis describes the development and implementation of a compact X-ray microtomography system called Tomo. Particular care was given to acquiring know-how and expertise in this investigation technique. The first step involved the development, the setup and tuning of the fundamental components for the construction of the experimental station: • the X-ray source, which is microfocus source, capable to generate very small focal spot sizes, typically between 5 and 50 microns in diameter. This is crucial to obtain high resolution images; • The linear stages with Stepper Motors for sample handling with a high degree of positioning accuracy (of the order of a micron). • The Flat-panel detectors, used for the projection radiography acquisition, that combine a large- area CMOS image sensor (CCD) and a scintillator. The second step was the development of a software package in LabView language (by National Instruments) for the remote control of the μTomo apparatus and the acquisition of radiographic images (projections). The software package can control the movement system, which is necessary for the alignment of the sample, the X-ray source and the detector. It also control the needed procedures for the acquisition and storage of the radiographic projections. The first experimental tests during the commissioning were particularly useful and allowed us to verify the performances of the μTomo experimental station. They were followed by a series of case studies that were carried out in various fields of material science.
Università della Calabria. Dipartimento di Fisica Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXXII
Keywords: x-ray tomography; X-ray Micro-CT; Cone-beam micro-CT; 3D imaging; Non-destructive analysis